2008
DOI: 10.1590/s1415-43662008000100006
|View full text |Cite
|
Sign up to set email alerts
|

Níveis de irrigação e doses de potássio sobre os teores foliares de nutrientes do maracujazeiro amarelo

Abstract: RESUMOEste trabalho foi realizado com o objetivo de avaliar o efeito de níveis de irrigação e doses de potássio aplicadas via água de irrigação por gotejamento, sobre os teores foliares de nutrientes do maracujazeiro amarelo. O trabalho foi desenvolvido no Campo Experimental da Fazenda Areão, da ESALQ/USP, em Piracicaba, SP (22°42' 30" S e 47°38' 00" W); utilizou-se, com tal propósito, um delineamento experimental de blocos ao acaso com quatro repetições, cujos tratamentos foram arranjados no esquema de parcel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
1
2
0
2
Order By: Relevance
“…The leaf content of calcium ranged from 8.18 (60%) to 20.71 g kg -1 (15%) with an average content equivalent to 13.57 g kg -1 . The values were below those observed by Sousa et al, (2008) and close to the values found by Martins (2009) and above those observed by Morais et al (2011). In the soil, the calcium content varied from 1.65 to 3.98 mg dm -3 , for the control and 60% organic compost treatment, respectively (Table 1).…”
Section: Biometsupporting
confidence: 76%
See 1 more Smart Citation
“…The leaf content of calcium ranged from 8.18 (60%) to 20.71 g kg -1 (15%) with an average content equivalent to 13.57 g kg -1 . The values were below those observed by Sousa et al, (2008) and close to the values found by Martins (2009) and above those observed by Morais et al (2011). In the soil, the calcium content varied from 1.65 to 3.98 mg dm -3 , for the control and 60% organic compost treatment, respectively (Table 1).…”
Section: Biometsupporting
confidence: 76%
“…The need for potassium by this crop needs to be determined and/or adjusted according to the cultivation and management system, considering that the recommendations of conventional fertilization with potassium in Brazil found in the literature are largely variable, from 50 to 530 kg of K 2 O ha -1 year (Borges et al, 2002). With reference to the evaluation of the nutritional status of yellow passion fruit plants by means of foliar diagnosis, Sousa et al (2008) verified that, even with the frequent application of potassium, the plants presented deficiency of this element, which according to the authors, can be attributed to plant age, leaf collection period, emission of flowers, tendrils, flower buds and fruit development. According to Freitas et al (2011) andAraújo et al, (2005), potassium is most required by the plants during fruiting, formation and maturation of the fruits, since this is the most important nutrient for passion fruit at this phase.…”
Section: Biometmentioning
confidence: 80%
“…Suprimento inadequado de potássio ocasiona o funcionamento irregular dos estômatos, podendo diminuir a assimilação de CO 2 e a taxa fotossintética (Montoya et al, 2006). Souza et al (2008) afirmam que maiores absorções de Ca, Mg e B pelo maracujazeiro ocorrem na ausência ou com pequenas doses de K aplicados, elementos estes que são essenciais para a formação das plantas e consequentemente, para formação dos frutos em termos de quantidade e qualidade. Diante do exposto, este trabalho teve como objetivo avaliar os frutos de pepino, em relação aos parâmetros pH, sólidos solúveis totais (%), acidez total titulável (g 100g -1 de amostra) e firmeza de polpa (kgf cm -2 ), a partir do cultivo em ambiente salino, utilizando dois tipos diferentes de manejo de fertirrigação e seis níveis iniciais de salinidade do solo em ambiente protegido, utilizando solo arenoso.…”
Section: Introductionunclassified
“…The climatic conditions in the experimental period are also related to the observed productivity. The rainfall was 908.3 mm from August to June, 11 months, being slightly below the annual regional average of 1,353.2 mm (CEPAGRI, 2017) and close to the levels of 1,293 and 944.2 mm year, verified by Carvalho et al (2000) and Sousa et al (2008), respectively, which guaranteed better crop yields, but in the harvest cultivation (40.9 t ha -1 and 41.3 t ha -1 ). Thus, the total water quantity was sufficient for the development of the crop in the present experiment, but it was distributed irregularly in the period (Figure 1), with a deficit in the months of October and December, which may have negatively influenced the productivity.…”
Section: Resultsmentioning
confidence: 61%